If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5 + -3x) + -8 = 88 (5 * 3 + -3x * 3) + -8 = 88 (15 + -9x) + -8 = 88 Reorder the terms: 15 + -8 + -9x = 88 Combine like terms: 15 + -8 = 7 7 + -9x = 88 Solving 7 + -9x = 88 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -9x = 88 + -7 Combine like terms: 7 + -7 = 0 0 + -9x = 88 + -7 -9x = 88 + -7 Combine like terms: 88 + -7 = 81 -9x = 81 Divide each side by '-9'. x = -9 Simplifying x = -9
| 3x-3=9-3x | | x/5/8=4/15 | | 21+x=25 | | (30-6)-8-3/2 | | -9x-11=3x+25 | | 3xn=18 | | 3.7x+5=2.7x | | 1=0.2x-0.9x-20 | | 110=2x+10 | | 6x+12=3(1) | | (6xy)^4/2xy^2 | | 6y+12=3(0) | | 6y+12=3(-1) | | 1100=(30-2X)(20-X)(X) | | X+17=23-6 | | -20=4/5n | | (3a-4)/7-(2a-3)/7 | | 6y+12=3(-2) | | 2-(T/3)=T/6 | | 50(28)=7(7(28)+4) | | 7=7x-8 | | -2x-6=2x+6x | | -2x-4=-9+5x | | 11x-2=8x-14 | | -3x-4=-9+5c | | 3x+8=3x+8x | | ((5x)/6) | | 5x-8=-7x-2 | | 329=1/2h(47) | | 10x+2=x-2 | | ((x^2)/3) | | 7(x+4)-2x-1=6 |